1998
DOI: 10.1046/j.1365-2222.1998.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA‐DR and ‐DQ alleles conferring susceptibility to pollen allergy and pollen associated food allergy

Abstract: We were able to identify HLA class-II alleles associated with some allergies thus indicating that these alleles might confer susceptibility to the respective allergens. Similarities at the level of the HLA class-II genotype parallel the empirical finding of distinct cross-reactivity patterns thus complementing investigations of IgE specificities. Our observations provide evidence for the major importance of antigen presentation on the manifestation of distinct crossreactivity patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…HLA has earlier been associated with allergy, playing a role in antigen/allergen presentation 35,36 and IgE dysregulation 37 ; however, the association is not clear and different alleles and allergies have been tested. Few studies have associated HLA DQ2/ DQ8 with allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA has earlier been associated with allergy, playing a role in antigen/allergen presentation 35,36 and IgE dysregulation 37 ; however, the association is not clear and different alleles and allergies have been tested. Few studies have associated HLA DQ2/ DQ8 with allergy.…”
Section: Discussionmentioning
confidence: 99%
“…One found an association between DQ8 and hevein-specific IgE immune response in individuals with latex allergy, 38 while others found DQ2 to be associated with olive pollen 39 and the allele DQB1*0301 to be associated with grass pollen allergy. 36 Thus, the association of HLA DQ2/8 with allergy remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1980s, Marsh et al [2] observed an association between an MHC-II-encoding HLA genotype and the immune response to the short ragweed pollen allergen Amb a 5 (Ra5). Since then, several HLA genotypes have been shown to be associated with respiratory and food allergies [3,4,5,6]. The correlation between an HLA genotype and sensitization to an allergen is strongest if the allergen contains a single immunodominant T cell epitope, as shown for the major mugwort pollen allergen Art v 1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are an association of HLA-DQ7 with cows' milk protein allergy in Italian children (Camponeschi et al, 1997), HLA-DRB1, DQB1, and DPB1 with peanut allergy (Howell et al, 1998), and HLA-DRB1*08 for peanut allergy (six-fold increased risk) and HLA-DRB1*12 (13-fold increased risk) for carrot allergy (Boehncke et al, 1998). Sénéchal et al (1999) described involvement of HLA-DR7 in the allergic response to apple and pollen, but concluded that the increased susceptibility conferred by HLA-DR7 was more related to atopy than to allergen-specific responses.…”
Section: Genetic Factors -Specific Immune-response Genesmentioning
confidence: 99%